Exploring Cognitive Skills and Academic Achievement in Geometry among Secondary Level Students in Nepal - Ghimire, Shree Prasad; Paudel, Krishna Chandra (Educational Journal, 2025)
Cognitive skills are essential for conceptual learning in geometry. In this study, the students' cognitive skills and academic achievement in learning geometry under four levels of cognitive domains have been explored through a mixed-method approach. Comprehensive analysis of the performance of students in geometry through achievement test have been used on the basis of Bloom's Taxonomy for Secondary Level Curriculum of Nepal in order to explore the cognitive skills of students. The achievement scores of geometry achievement test from the 32 students of grade IX in an institutional school located in Kathmandu district have been analyzed. The achievement scores were analyzed under gender, age, and correlations between different cognitive levels. The results of this study shows that the students' have high level of competencies in knowledge level problems (mean score: 8.59 out of 10) and faced greater challenges in higher ability thinking skills (mean score: 3.19 out of 10). Similarly, the scores based on gender pattern with male students' performance is higher in knowledge and application levels, whereas female students have better performance in understanding and higher ability levels. It is further suggested that the specific opportunities for targeted instructional interventions to enhance students' skills and achievement across all levels of cognitive domains, particularly in fulfilling the gap between conceptual understanding and practical aspects.